The Implementation of Information and Communication Technology (ICT) in English Foreign Language (EFL) Teaching - Elmahida, Hani; Elbalqis, Putri (Universitas Islam Negeri Raden Intan Lampung, 2021)
Information and Communication Technology (ICT) useful to support English Language Teaching (ELT) for foreign language. However, this world particularly needs human resources who mastering English material and modern technology. The objective of this paper was to examine the utilization of ICT while conduct autonomous learning also to ensure teachers' abilities in the implementation of social media technology to support English Foreign Language (EFL) teaching classes. The survey used with collecting data from several young teachers by descriptive-qualitative method. Data showed four from six respondents already known ICT as well, automatically those five young teachers have appropriate ELT tools by various social media. Basically, teachers understand how important student-centered to be conducted particularly in EFL classes. In contrast, it was not balanced with the idea to develop ICT while designing interactive modern learning classes. Then, one case was found in the previous survey to be precise with high school teachers. Senior teachers just utilize one or two ICT tools in the ELT classes. The limitation of tools could make the output and outcome of the learning process is not optimal. Furthermore, this paper shows the importance of ICT integration tools and ELT which should be mastered by teachers in 4.0 era.